일개 이차 병원에서 치료한 소아 급성 세균성 위장염 원인 및 특징 - 김성윤; Sung Yoon Kim; 김현정; Hyun-jung Kim; 신은혜; Eun Hye Shin; 은병욱; Byung Wook Eun; 안영민; Young Min Ahn; 송미옥; Mi Ok Song (Pediatric infection & vaccine, 2017)
목적: 소아 급성 세균성 위장염은 흔히 급성 바이러스성 위장염에 비해 더 심각한 증상을 일으킬 수 있다. 본 연구는 소아 급성 세균성 위장염 환자의 원인을 조사하고, 임상 양상을 알아보고자 하였다. 방법: 2011년 1월부터 2014년 12월까지 서울에 위치한 1개 이차 병원에서 급성 위장염 증상으로 진료받은 소아 환자들의 대변을 서울시 보건환경연구원으로 보내어 원인균 검사를 시행하였다. 결과에 따른 임상적인 특성은 소아 환자들의 의무기록을 통해 후향적으로 조사하였다. 결과: 총 664 대변 샘플 중 183개(27.6%)에서 원인균이 분리되었다. 2012년부터 검사가 시행되었음에도 불구하고, 황색포도알균이 가장 흔한 원인균이었다(39.3%). 월별 검출률은 8월이 24.6%로 가장 높았다. 캄필로박터균의 연령군에 따른 검출률은 12-19세 군에서 가장 높았다(16.7%, P =0.04). 혈변을 보인 환자들 중에서 캄필로박터균이 가장 흔하게 분리되었다(31.0%, P =0.04). C-반응단백질을 비교 시 살모넬라속균 또는 캄필로박터균이 분리된 군이 황색포도알균 또는 병원성 대장균이 분리된 군에 비해서 더 높았다(5.7±0.6 mg/dL vs. 2.1±0.3 mg/dL, P<0.01). 결론: 황색포도알균, 병원성 대장균, 캄필로박터균, 살모넬라속균이 소아 세균성 위장염의 중요한 원인 균이었다. 연령에 따른 원인균 차이, 임상 증상, 염증 지표를 고려하는 것이 원인균을 추정하는 데 도움이 될 수 있겠다. Purpose: Acute bacterial gastroenteritis (ABG) can cause more severe symptoms than acute viral gastroenteritis in children. This study was aimed at determining the etiologic trends and to examine the clinical characteristics of ABG in children. Methods: We sent stool samples from the children with acute gastroenteritis who were treated at a secondary hospital located in Seoul, Korea between January 2011 and December 2014 to Seoul Metropolitan Government Research Institute of Public Health and Environment to find the causative organisms. Clinical characteristics of patient were analyzed through a medical records review. Results: Out of 664 stool samples, 183 (27.6%) yielded bacterial pathogens. Staphylococcus aureus was the most common bacterial pathogen, found in 72 cases (39.3%), even though it was only tested for since 2012. The monthly isolation rate was the highest (24.6%) in August. The isolation rate of Campylobacter spp. by patient`s age group was high (16.7%) in the 12- to 18-year-age group (P =0.04). In patients with bloody stool, Campylobacter spp. was the most commonly isolated (31.0%, P =0.04). When comparing C-reactive protein, the Salmonella spp.- or Campylobacter spp.-isolated group showed higher values than the S. aureus - or pathogenic Escherichia coli -isolated group (5.7±0.6 mg/dL vs. 2.1±0.3 mg/dL, P <0.01). Conclusions: S. aureus, Salmonella spp., pathogenic E. coli , and Campylobacter spp. were important pathogens of ABG among children. Considering the differences in pathogens found according to age, a clinical symptom and inflammation index might be helpful in assuming the causative organism.